Control of insulin secretion by GLP-1 - Jones,B; Bloom,S; Buenaventura,T; Tomas,Catala ADD; Rutter,G (Peptides, 2018)
Stimulation of insulin secretion by glucagon-like peptide-1 (GLP-1) and other gut-derived peptides is central to the incretin response to ingesting nutriments. Analogues of GLP-1, and inhibitors of its breakdown, have found widespread clinical use for the treatment of type 2 diabetes (T2D) and obesity. The release of these peptides underlies the improvements in glycaemic control and disease remission after bariatric surgery. Given therapeutically, GLP-1 analogues can lead to side effects including nausea, which limit dosage. Greater understanding of the interactions between the GLP-1 receptor (GLP-1R) and both the endogenous and artificial ligands therefore holds promise to provide more efficacious compounds. Here, we discuss recent findings concerning the signalling and trafficking of the GLP-1R in pancreatic beta cells. Leveraging “bias” at the receptor towards cAMP generation versus the recruitment of β-arrestins and extracellular signal-regulated kinases (ERK1/2) activation may allow the development of new analogues with significantly improved clinical efficacy. We describe how, unexpectedly, relatively low-affinity agonists, which prompt less receptor internalisation than the parent compound, provoke greater insulin secretion and consequent improvements in glycaemia.